2016
DOI: 10.1111/dom.12689
|View full text |Cite
|
Sign up to set email alerts
|

Rates and predictors of hypoglycaemia in 27 585 people from 24 countries with insulin‐treated type 1 and type 2 diabetes: the global HAT study

Abstract: AimsTo determine the global extent of hypoglycaemia experienced by patients with diabetes using insulin, as there is a lack of data on the prevalence of hypoglycaemia in developed and developing countries.MethodsThis non‐interventional, multicentre, 6‐month retrospective and 4‐week prospective study using self‐assessment questionnaire and patient diaries included 27 585 patients, aged ≥18 years, with type 1 diabetes (T1D; n = 8022) or type 2 diabetes (T2D; n = 19 563) treated with insulin for >12 months, at 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
268
4
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 239 publications
(300 citation statements)
references
References 28 publications
23
268
4
5
Order By: Relevance
“…The higher rates displayed in Central and South American countries confirm the findings from a recent observational analysis (Hypoglycaemia Assessment Tool study), which reported a twofold greater risk of severe hypoglycaemia in individuals living in Argentina and Mexico [31]. On the other hand, our results for Asian countries were mixed and fewer data on the risk of hypoglycaemia in Asian populations are currently available.…”
Section: Discussionsupporting
confidence: 70%
“…The higher rates displayed in Central and South American countries confirm the findings from a recent observational analysis (Hypoglycaemia Assessment Tool study), which reported a twofold greater risk of severe hypoglycaemia in individuals living in Argentina and Mexico [31]. On the other hand, our results for Asian countries were mixed and fewer data on the risk of hypoglycaemia in Asian populations are currently available.…”
Section: Discussionsupporting
confidence: 70%
“…20 Furthermore, the slight difference in diabetes duration between responders and nonresponders may indicate that subjects with a higher hypoglycaemia risk may have been more inclined to respond since a longer duration has been shown to be associated with risk of hypoglycaemia in previous studies. 2 To conclude, this study shows that FoH is persistent over time if not treated and that hypoglycaemia frequency is the strongest predictor of FoH. Thus, asking patients about the occurrence of hypoglycaemia is of the utmost importance as is helping them adequately detect, prevent and treat hypoglycaemia.…”
Section: F I G U R E 1 Each Participant's Individual Scores On Hypoglmentioning
confidence: 66%
“…5 Past experience of SH is associated with greater fear of hypoglycaemia (FoH) in individuals with type 1 diabetes, suggesting that the experience of hypoglycaemia plays an important role in triggering FoH. 2,[6][7][8][9] FoH is recognized as a complex and common phenomenon affecting quality of life and diabetes management for individuals with type 1 diabetes. 9 Furthermore, worries about hypoglycaemia are also common in family members.…”
mentioning
confidence: 99%
“…The study population in Northern Europe/Canada had a longer disease duration and had used insulin for longer than the other regions, which might influence the level of hypoglycaemia awareness. For the overall HAT study population, HbA 1c was not found to be a significant predictor of hypoglycaemia 13. However, in people with Type 2 diabetes, the higher blood glucose cut‐off for defining hypoglycaemia occurred in regions with a higher mean HbA 1c (Middle East, Russia and South East Asia), perhaps suggesting that these participants experience hypoglycaemia at higher blood glucose levels.…”
Section: Discussionmentioning
confidence: 84%